Enhancement of soil health, germination and crop productivity in Andrographis paniculata (Burm.f.) Nees, an important medicinal crop by using a composite bio inoculant. (20th July 2021) - K., Premalatha; Botlagunta, Navya; D., Santhosh; Hiremath, Channayya; Verma, Rajesh K.; Shanker, Karuna; Sundaresan, V.; Kalra, Alok
Abstract: The untapped microbial communities in medicinal plants can have a genetically varied population with multi-functional plant growth promoting characters. An attempt was made to investigate the effect of bioinoculant, Cohnella sp., Chryseobacterium taklimakanense, Lysobacter soli and Paenibacillus glycanilyticus isolated from the medicinal plant ( Hemidesmus indicus ) rhizosphere on the growth parameters of Kalmegh ( Andrographis paniculata ) without chemical fertilizers. A vermicompost carrier based single, dual and multiple bio-inoculant formulation was developed and tested for the survival of individual strains, showed a maximum population of 1 × 10 6 cells g −1 after 90 days of storage at 28 ± 2 °C invariably in all formulations. The inoculums' efficiency on Kalmegh under greenhouse conditions resulted in boosted growth with the maximum plant height (95.8 cm) in Cohnella sp . application, followed by consortium of all strains recorded 91.5 cm. Flower initiation occurred sooner in plants inoculated with bacterial consortium of all as well in Cohnella sp. alone, consecutively resulted in highest Andrographolide content of 3.06% and 3.50%, respectively. Maximum fresh weight herbage yield of 39.5% and 27.5% (dry weight) was recorded in plants treated with bacterial consortium ( Cohnella sp, C. taklimakanense, L. soli and P. glycanilyticus) over non-inoculated control as well the available nitrogen, phosphorus and potassium content. Germination of seed experiment revealed the synergism of bacterial isolates in consortium for promoting plant growth. Further, the quanta of inoculums is reduced by 25 percent in composite inoculation, in turn reduces the fertilizers expenditure and persist until the harvesting stage of the crop with the need to apply once.